Impact of psoriatic disease on women aged 18 to 45: Results from a multinational survey across 11 European countries - Sandy R. McBride, MBBS, FRCP, MD; Maria C. Fargnoli, MD; Anne-Claire Fougerousse, MD; Marta García Bustínduy, MD, PhD; Louise Catton, BSc; Lerzan Senturk, MD; Cécile Ecoffet, PharmD; Jan Koren; Laura Andreoli, MD, PhD; Laura C. Coates, MBChB, MRCP, PhD; Alice Titialii, MSc (Wolters Kluwer, 2021)
ABSTRACT: Background: Plaque psoriasis (PSO) is a long-term inflammatory condition that can cause concomitant joint symptoms (psoriatic arthritis [PsA]) in up to 30% of patients. The impact of psoriatic disease on disease outcomes and quality of life is greater in women than men. Objective: We evaluated the impact of psoriatic disease on women aged 18 to 45 years across Europe. Methods: Women aged 18 to 45 years with moderate to severe PSO, PsA, or PSO + PsA (PSO with progression to PsA) and prior biologic experience were recruited from market research panels and patient association groups of the International Federation of Psoriasis Associations, European Federation of Psoriasis Patient Associations, and Arthritis Ireland and asked to complete a survey. Questions covered social and psychological wellbeing, employment, and family planning. Question types included 5- or 7-point agreement scales, where the highest/lowest two ratings were considered agreement/disagreement, respectively. The results are reported as proportions of those who selected the answer, divided by overall respondents for each question. Women were not required to answer all questions. Results: Survey respondents (N = 573) had a diagnosis of PSO (n = 236), PsA (n = 173), or PSO + PsA (n = 164). Women self-reported similar mean scores for physical (57.0 of 100) and mental (59.0 of 100) health. A fifth (21%) had not achieved their desired career due to PSO/PsA; career dissatisfaction and increased sick leave were linked to poor mental health. Some women reported having a limited social life (33%), smaller families (34%), and being more likely to adopt children (27%) due to PSO/PsA. A quarter of women (27%) reported not understanding enough about PSO/PsA (nonmembers vs. members of patient association groups: 37% vs. 8%). Conclusion: Our findings highlight the considerable burden of psoriatic disease on women of childbearing age. Increased provision of information tailored to women, training for health care professionals, and shared decision-making between patients and health care professionals may help better support women with psoriatic disease.